KUALITAS FISIK KERTAS SETELAH PENGERINGAN DENGAN METODE KERING ANGIN DAN VACUUM FREEZE DRYING - Syafurjaya, Roby; Hasanah, Sari (BACA: Jurnal Dokumentasi dan Informasi, 2009)
Disaster like flood, tsunami has bad impacts to the documents or archives. When exposed to water, papers and books absorb moisture. The following paper explains how two drying methods would affect wet papers. The physical characterization of papers dried by two drying methods was observed. The two drying methods used are air drying and vacuum freeze drying. After drying, the quality of paper had tendency to decrease compare to before absorbing water. For some parameters, the physical characterization of papers dried by air drying method was better than the physical characterization of papers dried by vacuum freeze drying.